Soil dissolved organic carbon in terrestrial ecosystems: Global budget, spatial distribution and controls - Ziyu Guo; Yihui Wang; Zhongmei Wan; Yunjiang Zuo; Liyuan He; Dan Li; Fenghui Yuan; Nannan Wang; Jianzhao Liu; Yanyu Song; Changchun Song; Xiaofeng Xu (Global Ecology and Biogeography, 2020)
Aims Soil dissolved organic carbon (DOC) is a primary form of labile carbon in terrestrial ecosystems, and therefore plays a vital role in soil carbon cycling. This study aims to quantify the budgets of soil DOC at biome and global levels and to examine the variations in soil DOC and their environmental controls. Location Global. Time period 1981–2019. Methods We compiled a global dataset and analysed the concentration and distribution of DOC across 10 biomes. Results Large variations in DOC are found among biomes across space and the soil DOC concentration declines exponentially along soil depths. Tundra has the highest soil DOC concentration in 0–30 cm soils [453.75 (95% confidence interval: 324.95–633.5) mg/kg], whereas tropical and temperate forests have relatively lower DOC concentrations, ranging from 30.20 (24.78–36.80) to 54.54 (49.77–59.77) mg/kg. DOC generally accounts for Main conclusions A global synthesis is combined with an empirical model to extrapolate the DOC concentration along soil profiles across the globe, and global budgets of DOC are estimated as 7.20 Pg C in the top 0–30 cm and 12.97 Pg C in the 0–100 cm soil profile, respectively, with a considerable variation among biomes. The strong soil texture control but weak total organic carbon (TOC) control on DOC variations suggest that the investigation of physical protection of soil organic carbon might need to expand to consider the labile C in soils. The global maps of DOC concentration serve as a benchmark for validating land surface models in estimating carbon storage in soils.